2023
DOI: 10.1001/jamanetworkopen.2023.31264
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone Use in Novel Potent Opioid and Fentanyl Overdoses in Emergency Department Patients

Alexandra Amaducci,
Kim Aldy,
Sharan L. Campleman
et al.

Abstract: ImportanceSynthetic opioids, such as the fentanyl analogue and nitazene drug class, are among the fastest growing types of opioids being detected in patients in the emergency department (ED) with illicit opioid overdose (OD). However, clinical outcomes from OD of novel potent opioids (NPOs), specifically nitazenes, are unknown aside from small case series.ObjectiveTo determine naloxone administration and clinical sequelae of patients who were in the ED with NPO overdose compared with fentanyl OD.Design, Settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…A second important finding of this study was that slowly dissociating agonists such as carfentanil were more resistant to antagonism by naloxone. There have been numerous reports of more naloxone, in the form of multiple or higher doses, being required to reverse overdoses involving fentanyls and nitazenes compared with heroin overdoses (Moe, Godwin et al ., 2020; Irvine, Oller et al, 2022; Amaducci, Aldy et al ., 2023). What may be occurring with the fentanyls may in fact be ‘over’ overdose, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second important finding of this study was that slowly dissociating agonists such as carfentanil were more resistant to antagonism by naloxone. There have been numerous reports of more naloxone, in the form of multiple or higher doses, being required to reverse overdoses involving fentanyls and nitazenes compared with heroin overdoses (Moe, Godwin et al ., 2020; Irvine, Oller et al, 2022; Amaducci, Aldy et al ., 2023). What may be occurring with the fentanyls may in fact be ‘over’ overdose, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For agonists and antagonists interacting at the same orthosteric binding site on a receptor a competitive antagonist such as naloxone would be expected to reverse all agonists equally given that the antagonist binds to the unbound receptor and prevents agonist binding rather than physically displacing the agonist from the receptor (Ritter, Flower et al ., 2024). However there have been numerous reports of more naloxone, in the form of multiple or higher doses, being required to reverse overdoses involving fentanyls and nitazenes compared with heroin overdoses (Moe, Godwin et al ., 2020; Irvine, Oller et al, 2022; Amaducci, Aldy et al ., 2023). Reduced sensitivity to naloxone has also been observed in animal studies using sub lethal doses of fentanyls (Hill, Santhakumar et al ., 2020; Elder, Varshneya et al ., 2023)…”
Section: Introductionmentioning
confidence: 99%
“…In a cohort study of adults admitted to emergency departments with a presumed OIRD it was found that those patients ( n = 9) who tested positive for brorphine [a potent, non-fentanyl–derived synthetic opioid ( 62 )] or various nitazenes required in-hospital doses of naloxone with a cumulative dose of 4.4 mg compared to those in the fentanyl-only group ( n = 11) with a cumulative dose of 6.41 mg. However, the non-fentanyl group was administered a statistically significantly higher number of in-hospital naloxone boluses compared with the fentanyl group, which suggests that brorphine and nitazenes may be more potent than fentanyl ( 63 ). As with synthetic opioids in general, better evidence is needed about the optimal naloxone doses, the delay between doses, and how many doses are ideally needed for treating nitazene overdoses ( 24 , 27 , 28 ).…”
Section: Treatment Of Oirdmentioning
confidence: 96%
“… 5 , 6 The highest rate of fatality from NPS was from synthetic opioids, which may require many times the dose of naloxone available in emergency departments with limited resources. 7 , 8 The numbers for OUD and opioid overdose deaths justify the term “opioid epidemic” used by both scientific and popular outlets and constitute a social and public health crisis that needs to be prioritized by implementing new prevention, treatment, and mitigation approaches, among them pharmacotherapy.…”
Section: Introductionmentioning
confidence: 99%